Double dropping down under: Correlates of simultaneous consumption of two ecstasy pills in a sample of Australian outdoor music festival attendees - Grigg, J.; Barratt, Monica; Lenton, Simon (Wiley-Blackwell Publishing Ltd., 2018)
Introduction and Aims: The term ‘double dropping’ refers to a person consuming two drugs simultaneously, typically two ecstasy pills. This practice has been reported in numerous countries, including Australia; however, the prevalence and correlates of double dropping among ecstasy users is unknown. Double dropping is particularly risky when adulteration of ‘ecstasy’ with novel substances and higher dosages of MDMA in pure ecstasy pills have both been increasingly reported. This paper investigates the prevalence and correlates of double dropping in a purposive sample of Australian festival-goers who used ecstasy at the last festival they attended. Design and Methods: A web survey was completed by almost 2000 Australian festival-goers. The analytic sample (n = 777) was 59% male and had a median age of 20 years (interquartile range 19–23). Results: Almost half (48%) of respondents who used ecstasy pills reported double dropping in association with the last festival attended. Multivariable logistic regression found respondents who were younger, male, more frequent ecstasy users, more frequent festival-goers, had a preference for electronic dance music, attended a multi-day festival and used ecstasy in pill form were at greater odds of reporting double dropping at the last festival attended. Discussion and Conclusions: Double dropping was a commonly reported practice among festival-goers in this purposive sample. While this practice may reflect historically low-dose ecstasy pills in Australia, the changing contexts of novel drugs and increasing MDMA purity may warrant consideration of harm-reduction interventions and drug-checking services which could help festival-goers make more informed decisions about drug dosage.